2013
DOI: 10.1002/cjce.21905
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation of flow regime maps in a slot‐rectangular spouted bed

Abstract: The recognition of flow regimes is very important in the application of spouted beds. In this paper, two‐dimensional computer simulations of a slot‐rectangular spouted bed using FLUENT commercial software were utilised to construct flow regime maps. Two‐phase gas–solid flows in the bed were simulated with computational fluid dynamics (CFD) using the two‐phase Eulerian–Eulerian granular model. The numerical simulations were applied to predict different flow regimes. The constructed flow regime map for a bed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Therefore, computational fluid dynamic (CFD) with advantages of simplicity, accuracy and efficiency, has become attractive in the research of many separation processes, such as distillation, absorption, crystallization etc. [3][4][5].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, computational fluid dynamic (CFD) with advantages of simplicity, accuracy and efficiency, has become attractive in the research of many separation processes, such as distillation, absorption, crystallization etc. [3][4][5].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…After the validation of their model, using particles with diameter 1.44 mm, Tabatabaei and colleagues [221] employed it to obtain the complete regime map of a slot-rectangular spouted bed containing particles of diameter 3.77 mm; the momentum exchange between the solid and gas phases was calculated through a drag law they previously developed [238], which is a modification of the Di Felice [162] drag law. Jin and others [207,214] simulated the fluid dynamics of a spouted bed used as food Microwave Vacuum Dryer, obtaining that both the jet penetration depth and the pressure drop have an almost linear dependence on the spouting velocity.…”
Section: Study Of the Fluidisation Behaviourmentioning
confidence: 99%
“…Number of Occurrences References k-ε 18 [90,92,203,204,206,209,211,212,[215][216][217][218][223][224][225][226][227][230][231][232],236] None or not specified 16 [25,89,91,202,203,205,207,208,210,213,214,[220][221][222]228,229] Riera and co-workers [217] simulated a multi-phase spouted column to test the validity of three turbulence models: the k-ε model, the k-ω model [240] and the SST model [241]. They observed that the k-ε and k-ω models yielded similar results for an air-water mixture, while the SST model was the most adequate for the air-water-sand mixture.…”
Section: Modelmentioning
confidence: 99%